2021
DOI: 10.1063/5.0035178
|View full text |Cite
|
Sign up to set email alerts
|

Serrated slat cusp for high-lift device noise reduction

Abstract: Noise reduction capabilities of slat cusp serration were experimentally assessed and demonstrated for a 30P30N three-element high-lift airfoil fitted with two different types of serrated slat cusp. Aerodynamic characteristics were evaluated with the aid of surface pressure distribution and insignificant differences were found amongst all the tested configurations. The unsteady flow characteristics of the slat serrations were examined using near-and far-field measurements to gain a deeper understanding of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…[6][7][8] Equally important, the turbulent inflow has a profound impact on turbulence interaction noise; specifically, an increase in turbulence length scale and turbulence intensity results in increased noise spectra levels. 9,10 Reduction of aerodynamically generated noise is proven to be effective through the means of passive flow control, be that through the use of serrations [11][12][13][14][15][16][17] or porous materials. [18][19][20][21][22][23][24] Serrations have been the subject of many studies for the reduction of turbulence interaction noise due to their ease of implementation; 16,[25][26][27][28] however, they require a fundamental change to the design of the airfoil geometry at the leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Equally important, the turbulent inflow has a profound impact on turbulence interaction noise; specifically, an increase in turbulence length scale and turbulence intensity results in increased noise spectra levels. 9,10 Reduction of aerodynamically generated noise is proven to be effective through the means of passive flow control, be that through the use of serrations [11][12][13][14][15][16][17] or porous materials. [18][19][20][21][22][23][24] Serrations have been the subject of many studies for the reduction of turbulence interaction noise due to their ease of implementation; 16,[25][26][27][28] however, they require a fundamental change to the design of the airfoil geometry at the leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies were primarily conducted in wind tunnels with size limitations, where the transition from laminar flow regime to turbulent flow regime is unlikely to occur due to the size of the test models. In order to achieve a turbulent flow over the airfoil, or at least over the trailing edge, and to mimic the conditions at high Reynolds number flow that the actual wings experience, a tripping tape is utilized to force an early (forced) transition to the turbulent regime over the airfoils in experiments [36][37][38][39][40]. Despite its utilization in almost all experiments, the number of investigations addressing the effect on mean quantities is limited [41][42][43] and frequency dependent effect does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various bionic serrated devices had been studied by simulation or experimental methods. 33,34 Jawahar et al 35 found that the slat serrations made a reduction of up to 5 dB in the overall energy level, and the acoustic mechanism was analyzed by higher-order spectral analysis and wavelet analysis. The sawteeth were effective in terms of the suppression of scattering waves.…”
Section: Introductionmentioning
confidence: 99%